Aggressive Disease Course of Multiple Myeloma with Concomitant ALK-Negative Anaplastic Large Cell Lymphoma: A Case Report with an Unusual Presentation - Michela Staderini; Lara Mannelli; Elisabetta Antonioli; Benedetta Puccini; Valentina Berti; Francesco Mungai; Federica Vergoni; Valentina Carrai; Luigi Rigacci; Alberto Bosi (Case Reports in Hematology)
ALK-negative anaplastic large cell lymphoma is a rare T-cell neoplasm with an aggressive course requiring prompt diagnostic work-up and treatment. Few cases of concomitant multiple myeloma and T-cell neoplasm are described in the literature, mainly regarding primary cutaneous anaplastic large cell lymphoma. We present the case of a 65-year-old man, simultaneously diagnosed with ALK-negative anaplastic large cell lymphoma with extranodal localization in the gastrocnemius muscle (stage 1AE) and IgG lambda multiple myeloma (ISS 2, Durie-Salmon stage 3A). Both diseases required therapeutic intervention due to the high proliferative index of lymphoma and the presence of bone lesions attributable to myeloma. The therapeutic program initially included chemotherapy (cyclophosphamide, doxorubicin, vincristine, etoposide, and prednisone; CHOEP), radiotherapy on the leg, bortezomib, and then consolidation with autologous hematopoietic stem cell transplantation. Despite being on bortezomib treatment and waiting for transplantation, the patient experienced an early myeloma progression that turned out to be refractory to second-line lenalidomide-based treatment. To our knowledge, this is the first case of concurrent diagnosis of extranodal ALK-negative anaplastic large cell lymphoma of the muscle and multiple myeloma. Simultaneous onset can be challenging for clinicians as both diseases may have an aggressive course requiring multiple treatments with increased risk of toxicity and complicated management.